Science Accounting Agency Theory Review from the Perspective of Javanese Cultural Values (Study on BMT WM) - Mahsuni, Abdul Wahid (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The research method used in this study can be classified in interpretive paradigm, as a paradigm that emphasizes language role,interpretation, and comprehension in social science. The technigue of data analysis employed is HANACARAKA, reflecting that human represents the image of God who naturally has creative force, sense, and wish: which are an entity in the sense of the existence of the universe, God and human could not be separated each other. The result of this study shows that Javanese culture contains a Superior value that is religious nuance, where power and responsibility delegating in Javanese culture is a manifestation of human as the God's Subordinate on earth. With the presence of trustfulness metaphor in Organization could decrease agency cost (agency cost of equity) because the form of responsibility other than to the principal is to God as well, but 'Conversely if the agent cannot be trusted then the agency cost (agency cost Of equity) will be higher because the agents do not have responsibility to the principal or God, but that is only for maximizing their own utilities. Therefore, in Javanese culture, agent and principal responsibilities are not limited to the contract dealt, but responsibility to God as well